Medios de comunicación digital y su expansión en el cantón Ventanas - Porro Fajardo, Deliyer Charles (2022)
This case study seeks the analysis of digital media, new technologies and the development of digital journalism that is of utmost importance for the dissemination of rapid information for the benefit of the society of the Canton Ventanas Province of Los Ríos. To know the needs and opinions of the population, a survey was conducted with various questions based on digital media versus traditional media and it was found that citizens prefer digital media and social networks to be in constant communication. In the Canton of Ventanas, Province of Los Ríos, the digitalization of the media began when the global pandemic, caused by Covid-19, abruptly changed the socio-comunicacional reality, that is, the digital media played a fundamental role in the dissemination of information to be immediate and timely. Society saw this new mode of communication as optimal because all the events that were taking place were already being shared on various social platforms such as Facebook and Twitter. Without a doubt, the advancement of technology is a phenomenon that has helped people's lives where basically all human activity takes place around the internet and new technologies.